Association of TNF-α polymorphisms rs1800629 (−308G>A) and rs361525 (−238G>A) with type 2 diabetes mellitus in the Punjabi population of Pakistan - Waqar, Muhammad; Tai, Tsai-Sung; Qadeer, Abdul; Aziz, Umar; Abohassan, Mohammad; Chen, Chien-Chin; Khan, Sawar (Frontiers in Endocrinology, 2025)
BackgroundThe TNF‐α -promoter polymorphisms rs1800629 (−308G>A) and rs361525 (−238G>A) have been variably associated with type 2 diabetes mellitus (T2DM) risk in different populations. This study evaluated these two polymorphisms in a cohort of Punjabi individuals from Pakistan.MethodsA case–control study was conducted including 100 clinically diagnosed T2DM patients and 100 healthy controls. Genotyping of TNF‐α rs1800629 and rs361525 was performed using allele‐specific ARMS-PCR and validated by sequencing. Allele and genotype frequencies were compared between groups, odds ratios (ORs) and 95% confidence intervals (CIs) were calculated, and Hardy–Weinberg equilibrium was assessed.ResultsThe A alleles of rs1800629 and rs361525 were significantly more frequent in T2DM cases compared to controls (3.68% vs. 0.54%, OR = 6.779, p = 0.037 for rs1800629; 5.26% vs. 0.53%, OR = 9.684, p = 0.006 for rs361525). Fasting blood sugar level (FBS) of 150 ± 45 mg/dL was recorded in diabetic subjects. Multivariate and forest plot analyses supported the association of both variants with increased T2DM risk. Control group genotypes conformed to Hardy-Weinberg equilibrium, validating population stability.ConclusionIn this Punjabi cohort from Pakistan, the A alleles of TNF-α promoter polymorphisms rs1800629 and rs361525 were significantly more frequent in T2DM cases, indicating that these variants increase susceptibility to T2DM in this population.